Perbandingan perlindungan ahli minoriti dalam undang-undang syarikat di Malaysia dan Indonesia / Donny Indra - Donny, Indra (2005)
This thesis is a comparative study of the protection given to minority members under Company Law in Malaysia and Indonesia. Companies play an important role in the economy of a country and the welfare of its people. A substantial part of the citizen's wealth is invested in companies. If companies are strong and progressive, the nation and its citizens will prosper. A company must raise its capital from its members or the public. The citizens of a country wilJ not invest in companies unless their rights are protected. Protection of the rights of members a company, especially the minority members, becomes an important topic to be discussed in Company Law. Company Law of Malaysia is inherited from England and Australia. Malaysia's Company Law has many rules that govern the protection of the rights of the minority member. They are based on both statute law and court decisions. Malaysian Company Law on the protection of the minority member has its strong and weak points, as will be presented and elaborated in this thesis. Indonesia's Company Law is mainly based on European law. Like Malaysian law it takes into account the rights of the minority and tries to protect these rights. Its rules are based on a 1995 statute, Undang-Undang tentang Perseroan Terbatas. Indonesia law is new and many of its statutory rules await judicial interpretation. Indonesian law like Malaysian law has its strength and weaknesses. In this thesis an attempt is made to make a comparative study of how Company Law attempts to protect the minority members in Malaysia and Indonesia The Miter will attempt to analyse the rules on minority protection in the two countries and compare their respective approaches to the subject. This is an interesting study because it compares the traditional and weJJ-tested approach of a Common Law system to the new and untested menthods of the Indonesian statute. A vital question is whether the present law in Malaysia and Indonesia adequatly protects the minority. The thesis will attempt to demonstrate that both countries need to review their legal rules on minority protection to enhance minority protection. To achieve this purpose this thesis has suggested many amendments to the law in both countries. This thesis will also demonstrate that each country can learn from the other to improve its Jaws on minority protection.